Anisomycin sensitizes non‐small‐cell lung cancer cells to chemotherapeutic agents and epidermal growth factor receptor inhibitor via suppressing PI3K/Akt/mTOR. (31st December 2020) - Tan, Hongxia; Hu, Biao; Xie, Fan; Zhu, Chuanbing; Cheng, Zhenshun
Abstract: The poor outcomes in advanced non‐small‐cell lung cancer (NSCLC) necessitate new treatments. Recent studies emphasize anisomycin as a promising anti‐cancer drug candidate. In this work, we systematically investigated the efficacy of anisomycin alone and its combination with the standard‐of‐care drugs in NSCLC. We showed that anisomycin inhibited growth, migration, and survival in NSCLC cells regardless of genetic mutation status, and to a greater extent than in normal lung epithelial cells. Isobologram analysis showed that the combination of anisomycin with cisplatin, paclitaxel, or gefitinib was synergistic in NSCLC but not normal lung cells. We further demonstrated that anisomycin inhibited NSCLC growth in mice. The combination of anisomycin with cisplatin was more effective than cisplatin alone and completely arrested NSCLC growth throughout the whole duration of treatment. JNK and p38 MAPK were not required for anisomycin's action. In contrast, anisomycin inhibits PI3K/Akt/mTOR pathway. Overexpression of constitutively active Akt reversed the pro‐apoptotic effect of anisomycin. Our work demonstrates the selective anti‐NSCLC activity of anisomycin via suppressing PI3K/Akt/mTOR. Our findings provide preclinical evidence to initialize the clinical trial of using anisomycin to sensitize NSCLC to current therapy.